Mapping the Landscape of Critical Thinking Assessment in STEM Education: A Systematic Review of Psychometric Properties, Contextual Implementation, and Future Directions - Mudi, Yuleks Juru; Hidayati, Kana; Nursa'ban, Muhammad; Pusporini, Widowati (Integrated Science Education Journal, 2026)
Purpose of the study: This study aims to systematically map the landscape of critical thinking assessment in STEM education, with a particular focus on psychometric characteristics, contextual implementation, and emerging research trends. Methodology: A Systematic Literature Review (SLR) was conducted following the PRISMA protocol using the Scopus database as the primary source. A total of 58 studies published between 2018 and 2025 were analyzed through bibliometric mapping using VOSviewer and thematic synthesis. Main Findings: The findings indicate a substantial increase in research on critical thinking assessment in STEM education since 2020, aligning with growing global attention to 21st-century competencies. However, most studies continue to position assessment primarily as a tool for evaluating learning outcomes or the effectiveness of pedagogical interventions, such as project-based, problem-based, and inquiry-based learning. Only a limited number of studies systematically examine the psychometric quality of assessment instruments, including evidence of construct validity, reliability, and multidimensional structure. This pattern reveals a clear gap between assessment practices in STEM education and established standards for educational measurement, which may lead to weak or potentially misleading conclusions about students’ critical thinking abilities. Novelty/Originality of this study: This review integrates bibliometric and thematic analyses to identify conceptual and methodological gaps in the existing literature and proposes a coherent direction for the development of critical thinking assessments that are both psychometrically robust and contextually relevant within STEM education.